A Survey of Hospital Pharmacy Guidelines for the Administration of 3% Sodium Chloride in Children - Siddharth A. Shah; Juan C. Ayus; Michael L. Moritz (MDPI AG, 2022)
Three percent sodium chloride (3% NaCl) is the treatment of choice for symptomatic hyponatremia. A barrier to the use of 3% NaCl is the perceived risk of both local infusion reactions and neurologic complications from overcorrection. We examine whether children's hospital pharmacies have policies or practice guidelines for the administration of 3% NaCl and whether these pharmacies have restrictions on the administration of 3% NaCl in terms of rate, route, volume and setting. An Internet survey was distributed to the pharmacy directors of 43 children's hospitals participating in the Children's Hospital Association (CHA) network. The response rate was 65% (28/43). Ninety-three percent (26/28) of pharmacy directors reported a restriction for the administration of 3% NaCl, with 57% restricting its use through a peripheral vein or in a non-intensive care unit setting, 68% restricting the rate of administration and 54% restricting the volume of administration. Seventy-one percent (20/28) reported having written policy or practice guidelines. Only 32% of hospital pharmacies allowed 3% NaCl to be administered through a peripheral IV in a non-intensive care unit setting. The majority of children's hospital pharmacies have restrictions on the administration of 3% NaCl. These restrictions could prevent the timely administration of 3% NaCl in children with symptomatic hyponatremia.